Effectiveness of Oral Clonidine & Oral Gabapentin in Attenuation of Haemodynamic Stress Response to Laparoscopic Cholecystectomy - Talukder, Hasan Ali; Rashid, Muhammad Mamun Ur; Rahman, Md Abdur; Das, Shukha Ranjan; Mondol, Mohammad Shaddam Hossain (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: In laparoscopic surgery, Carbondioxide (CO2) is routinely used to create pneumoperitoneum.Elevated intra-abdominal pressure, due to pneumoperitoneum, and Carbondioxide (CO2) insufflationhave adverse effects on the cardiovascular system. Plasma level of catecholamines and vasopressin areincreased immediately after pneumoperitoneum. Increased catecholamine level activates the renin–angiotensin–aldosterone system, leading to characteristic hemodynamic alterations such as decreasedcardiac output, elevated arterial pressure and increased systemic/pulmonary vascular resistance. Variousdrugs have been used to attenuate these hemodynamic responses. Objectives: Purpose of this study was to evaluate the efficacy of oral Clonidine and oral Gabapentinpremedication in attenuation of haemodynamic stress responses to laparoscopic cholecystectomy. Setting & study design: This Placebo control study was conducted in Department of Anaesthesiologyand ICU, Dhaka Medical College Hospital from 1st March 2015 to 31st August 2015. Total 60 patients withASA grade I, II and planned for elective laparoscopic cholecystectomy were selected. Exclusion criteriawere patients with history of hypersensitivity to Clonidine, Gabapentin, and patients with chronic pain,history of cardiovascular, psychiatric disease, use of psychotropic drugs, pregnancy other comorbidcondition- CKD, COPD, IHD etc. Study subjects were allocated in to groups as placebo or control group(or Group P), gabapentin (300 mg) or Group G and clonidine (100 ìg) or Group C. Tested drugs were given75 to 90 minutes before surgery as oral premedication. All groups were compared for sedation, anxietylevel along with changes of haemodynamic status. Result: Majority of patients (40%) belongs to age 41 to 50 yrs. Out of 60 cases 55% were male and 45%were female. Male – female ratio was 1.22:1. A clear increase in sedation and a moderate decrease inanxiety were observed in both premedicated groups as compared with control groups. Preoperativeanxiolysis and sedation was higher in oral clonidine group as compared with Gabapentin group. Comparedwith group P, gabapentin & clonidine group showed statistically significant decrease in heart rate beforeinduction (98, 80, 74 beat/min respectively). The heart rate increased significantly immediately afterintubation in control group P, whereas no such changes were observed in group G and in group C (132,125, 112 beat/min respectively). After laparoscopy, the attenuation of mean arterial blood pressure inpremedicated group was statistically significant as to control group (Group P) and remained stabilizedduring intraoperative period. Study showed that premedication (Group C and G) patients werecomparatively well oriented and were able to obey commands than control (Group P) in the postoperativecare unit. Postoperative analgesic need was much less with gabapentin (Group G) and clonidine group(Group C) as compared with control (Group P). Conclusion: The gabapentin and clonidine are effective oral premedicant drugs with safe and multimodaldrug profile as they cause sedation, anxiolysis, and analgesia, with successful attenuation of thehemodynamic response of laparoscopy. Efficacy of Clonidine is superior to other also proven. JBSA 2020; 33(2): 48-54